Odourless Natural Rubber (ONR) - Nornanysya F K; Aminah S M Sharifah; Azemi S (Journal of Rubber Research, 2013)
Unplesant odour produced by natural rubber, in particular during mastication of standard Malasian Rubber (SMR 20) is objectionable to some workers. The issue of unplesant odour of natural rubber has long been raised both by the rubber industry and the public. However, until today there seems to be no effective solution to overcome the problem. In view of this situation, work has initiated to develop odourless Natural Rubber (ONR). This paper discusses the work to investigate and identify microorganisms that are responsible for unpleasant odour. Samples of odourous cuplumps were taken from the SMR factory of Malasian Rubber Board in Sungai Buloh. Microorganism isolated from cuplumps were identified by means of VITEK 2 system. The odourous compounds produced were collected using solid-phase microextraction (SPME) before being subjected to Gas Chromatography Mass Spectrometry (GCMS) to analyse the odour. Samples were analysed on a day to day basis for six days to determine the most odourous compounds. The volatile compounds detected at early incubation period were mainly hydrocarbons. Other volatile compounds produced throughout the incubation were low molecular weight compounds such as volatile fatty acids, sulphurous compounds, amino compounds, esters and alcohols. Three different antimicrobial agents were used to suppress the growth of odourous microorganisms during storage of cuplumps before processing. The SPME/ GCMS analysis provided experimental evidence that sodium hypochlorite and formaldehyde were able to inhibit the growth of microbes and suppressed the unpleasant odour of rubber. This rubber is now called Odourless Natural Rubber (ONR). Mixing was conducted on ONR to evaluate cure characteristics and physical properties of the vulcanised rubber based on ACSI mix formulation. ONR enhanced the cure rate and physical properties such as tensile strength, hardness and resilience which were higher than the control (SMRL).
Keywords: Bacteria inhibition; Cure characteristics; Natural rubber odour; Odourless NR; Processing safety; Tensile strength